Pengelolaan Kesan Daâ€™i dalam Kegiatan Dakwah Pemuda Hijrah - Uwes Fatoni; Annisa Nafisah Rais (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2018)
The phenomenon of â€œyouth Islamic preacher or daâ€™iâ€ who actively interact in Islamic teaching in mosques is a good news. They preach Islamic teaching using different approaches but accepted by young moslem people. These new and innovative methods makes da'wah interesting. The purpose of this research is to know management of impression of young Daâ€™i, named Ustadz Handy Bonny in conveying his dakwah messages. This study used Erving Goffman's Impression Management study with qualitative method, Dramaturgi approach. The result of this research shows that Ustadz Handy Bonny performs impression management by producing good image in public. He uses social media as a stage in da'wah with interesting themes and designs, he also wear "casual" that accepted by difference young moslem people. He also behave in polite, relaxed, non-patronize, using soft language, keep ethics. By knowing the Impression Management of Daâ€™i, it is hoped that daâ€™i or Islamic preacher of da'wah can performed impression management properly so that the purpose of da'wah to change people to the Islamic way can be achieved easily.